FORMULASI PEMBUATAN PERDA NOMOR 6 TAHUN 2012 FORMULASI PEMBUATAN PERDA NOMOR 6 TAHUN 2012FORMULASI PEMBUATAN PERDA NOMOR 6 TAHUN 2012FORMULASI PEMBUATAN PERDA NOMOR 6 TAHUN 2012 FORMULASI PEMBUATAN PERDA NOMOR 6 TAHUN 2012 FORMULASI PEMBUATAN PERDA NOMOR - Dewi, Hevi Mariyana; S, Hermini; Windiani, Reni (Journal of Politic and Government Studies, 2014)
ABSTRACTThe purpose of this study is to analyze menganilisis manufacture of formulations Regional of Regulation No. 6 of 2012 on waste in the city Semarang. This study used a descriptive method with qualitative data. Data obtained from interviews.Based on the results, it can be concluded that the process of formulating the draft local regulations is not ideal and can be categorized into the institutional model. Elements or factors that affect composed of external elements of support is quite good but the involvement of outside elements less representative. Elements within the limited means and technology lead technical agency can not provide supporting data, the coordination and communication link that exists involves three parties (executive, legislative, and stakeholders). The main actors are and Sanitation Department, Department of City Planning and the Department of Public Works & Highways NRM Parliament Semarang and Semarang. The main actors are and Sanitation Department, Department of City Planning and the Department of Public Works & Highways NRM Parliament Semarang and Semarang. When viewed from the actors involved, the process of policy formulation can also be categorized into the elite models.Department of City Planning, Department of Hygiene and, Department of Public Works & Highways PSDA Semarang and Semarang City Council in formulating the draft regulation should pay more attention to the growing issue in society, open access to public disclosure broadly, prepare supporting data accurately , and implementing all phases of the formulation of draft local regulations.Keywords: Public Policy, Policy Formulation, and Waste Management